Effect of a denture cleanser on hardness, roughness and tensile bond strength of denture liners - Antônio de Luna Malheiros-Segundo; Marina Xavier Pisani; Helena de Freitas Oliveira Paranhos; Raphael Freitas de Souza (Universidade Estadual de Campinas, 2008)
Aim: This study aim to investigate the effect of a denture cleanser on hardness, roughness and tensile bond strength of a rigid (Kooliner) and a soft denture liner (Elite Soft) after 7, 60 and 120 days of immersion. Methods: Thirty circular and twenty rectangular specimens of each material were randomly distributed in two groups: control - immersion in artificial saliva at 37°C; and experimental - immersion in artificial saliva at 37ºC combined with immersion in the cleanser for 5 min. Hardness was measured using either a Vickers or Shore A hardness tester, and a surface roughness tester was used to measure the surface roughness. Tensile bond strength was carried out on a universal testing machine. Data were analyzed statistically by ANOVA or Kruskal-Wallis test (α=0.05). Results: No significant difference was found between the groups for the tested properties (p>0.05). There was an increase in the hardness of both materials after 60 days (p>0.05). No difference between the immersion periods was found for the roughness of Kooliner (p>0.05), although the roughness of Elite Soft decreased after 120 days in both groups (p>0.05). Kooliner presented higher tensile bond strength than Elite Soft (p>0.05). Conclusions: Both materials showed alterations on the tested properties during the experimental period, but these changes were not promoted by the denture cleanser.